Late miscarriage and stillbirth in asymptomatic and symptomatic hospitalised pregnant women in Belgium during the first and second waves of COVID-19: a prospective nationwide population-based study - An Vercoutere; Mbiton Joel Zina; Karolien Benoit; Elena Costa; Sara Derisbourg; Michel Boulvain; Kristien Roelens; Griet Vandenberghe; Caroline Daelemans; on behalf of the B. OSS collaborating group (BMC, 2023)
Abstract Background Stillbirth has been recognized as a possible complication of a SARS-CoV-2 infection during pregnancy, probably due to destructive placental lesions (SARS-CoV-2 placentitis). The aim of this work is to analyse stillbirth and late miscarriage cases in unvaccinated pregnant women infected with SARS-CoV-2 during the first two waves (wild-type period) in Belgium. Methods Stillbirths and late miscarriages in our prospective observational nationwide registry of SARS-CoV-2 infected pregnant women (n = 982) were classified by three authors using a modified WHO-UMC classification system for standardized case causality assessment. Results Our cohort included 982 hospitalised pregnant women infected with SARS-CoV-2, with 23 fetal demises (10 late miscarriages from 12 to 22 weeks of gestational age and 13 stillbirths). The stillbirth rate was 9.5‰ for singleton pregnancies and 83.3‰ for multiple pregnancies, which seems higher than for the background population (respectively 5.6‰ and 13.8‰). The agreement between assessors about the causal relationship with SARS-Cov-2 infection was fair (global weighted kappa value of 0.66). Among these demises, 17.4% (4/23) were "certainly" attributable to SARS-CoV-2 infection, 13.0% (3/23) "probably" and 30.4% (7/23) "possibly". Better agreement in the rating was noticed when pathological examination of the placenta and identification of the virus were available, underlining the importance of a thorough investigation in case of intra-uterine fetal demise. Conclusions SARS-CoV-2 causality assessment of late miscarriage and stillbirth cases in our Belgian nationwide case series has shown that half of the fetal losses could be attributable to SARS-CoV-2. We must consider in future epidemic emergencies to rigorously investigate cases of intra-uterine fetal demise and to store placental tissue and other material for future analyses.